Rumen fermentation patterns in buffalo bulls fed total mixed ration supplemented with exogenous fibrolytic enzyme and/or live yeast culture (Journal of Advanced Veterinary and Animal Research, 2015)
The objective of this study was to evaluate the effect of exogenous fibrolytic enzyme (EFE) and/or live yeast culture supplementation in total mixed ration (TMR) on rumen fermentation patterns in buffalo. For this, four adult buffalo bulls weighing 377.05±43.36 kg were randomly allotted to four dietary treatments viz., TMR containing R:C ratio of 70:30 (T1), T1 supplemented with EFE at 15 g/animal/day (T2), T1 supplemented with live yeast culture at 10 g/animal/day (T3), and T1 supplemented with EFEs at 15 g/animal/day and live yeast culture at 10 g/animal/day (T4). Rumen liquor from the fistulated animals was collected at 0, 1, 2, 4, 6 and 8 h post-feeding, and was analyzed. This study revealed that rumen pH values were highest at 0 h, and were declined to minimum by 4 h post-feeding, while total volatile fatty acids (TVFA), ammonia nitrogen (NH3-N), and nitrogen (N) fractions reached to peak at 4 h post-feeding, and later followed a decreasing trend in all the treatments. Supplementation of EFE in TMR (T2) had no effect (P>0.05) on rumen pH and food and protozoal N concentration, while it influenced to increase (P